Correction to: Human tissue-specific MSCs demonstrate differential mitochondria transfer abilities that may determine their regenerative abilities - Swati Paliwal; Rituparna Chaudhuri; Anurag Agrawal; Sujata Mohanty (Stem Cell Research & Therapy, 2019)
The original article [1] contains errors in Fig. 1. The authors noticed a potentially misleading aspect of the original article Fig. 1 where representative flow cytometry data for different panels were from different data sets and thus the gates were not in the same line. This may cause confusion to the readers who attempt to compare panels and, thus the amended Fig. 1 shown ahead represents data from a single data set that is suitable for between panel comparisons.